(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Congenital Tuberculosis was diagnosed in a 40-days-old premature infant. The infant had fever. A chest radiograph showed infiltrates which was thought to be bacterial infection. Gastric aspirate revealed acid- fast bacilli by Ziehl-Neelsen staining and fluorescent microscopy later confirmed to be Mycobacterium tuberculosis by Gene Xpert MTB/RIF test. Her 22 years old mother was later diagnosed as a case of tuberculosis with symptoms, signs and radiologic manifestation of mild pleural effusion with infiltration. Infant was treated with isoniazid, syrup rifampicin, pyrazinamide and pyridoxine and mother with RNTCP Cat I regimen. SAARC J TUBER DIS HIV/AIDS, 2016;XIII (1), page: 43-45